Critical thinking and the sustainable development goals: sustainable communities and cities. (Revista Cientifica Ingenio Magno, 2022)
It is part of a macro-project in which we worked with five teachers andsix courses and in this research, it was carried out with a course led by a teacher in theResearch Methodology space. Objective: we wanted to establish the level of constructionof knowledge and skills on critical thinking and the Sustainable Development Goals with thestudents of this course, during a semester. Assessments were made: one at the beginning ofthe course and another at the end of the semester. In the time between the evaluations,immersion in concepts of climate change, global warming and critical thinking waspromoted, based on articles and other readings. Based on the evidence, it was observedthat students, without guidance in the classroom, have very little interest in these issues, butwhen they are motivated, interesting commitments are found, which justifies and is essentialfor their execution in the academy to develop changes. that sustainable processes need.
Keywords: Education for Sustainable Development, Sustainable Development Goals, Moors, Critical Thinking.